A Highly Stretchable, Fiber‐Shaped Supercapacitor1. Issue 50 (8th November 2013) - Yang, Zhibin; Deng, Jue; Chen, Xuli; Ren, Jing; Peng, Huisheng
<x xml:space="preserve">Abstract</x> Superstretchy: A supercapacitor with high stretchability has been developed by wrapping two layers of sheets built of aligned carbon nanotubes, which serve as two electrodes, on an elastic fiber. The use of these sheets offers high flexibility, tensile strength, electrical conductivity, and mechanical and thermal stability. The supercapacitor shows and maintains a high specific capacitance after stretching for many cycles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>